Unpacking Violence: Examining Socioeconomic, Psychological, and Genetic Drivers of Gun-Related Homicide and Potential Solutions - John Menezes; Kavita Batra (Urban Science, 2025)
Background: Gun-related homicide remains a persistent public health crisis in the United States, with over 48,000 firearm-related deaths reported in 2022, including 19,651 homicides and 27,032 suicides. Despite frequent calls for tighter gun control, firearm access alone does not explain the complexity of violence. Objective: This commentary aims to unpack the socioeconomic, psychological, and biological drivers of gun-related homicide and propose integrative, evidence-based solutions that extend beyond legislative reform. Methods: We synthesized data from peer-reviewed literature, national crime and health databases (e.g., Centers for Disease Control and Prevention and Federal Bureau of Investigation), and international reports. We examined patterns related to poverty, trauma, male aggression, neurobiology, and firearm acquisition, as well as cross-national comparisons with countries like Switzerland and Mexico. Findings: Young males, particularly those aged 10–29, accounted for 50% of homicide offenders in 2022. African Americans experienced homicide rates of 23.1 per 100,000, ten times the rate among Whites. Up to 56% of incarcerated men report childhood physical trauma, and over 40% of those in prison exhibit symptoms of serious mental illness. While firearm legislation varies widely, analysis reveals that over 90% of crime guns are acquired illegally or through informal sources. International comparisons show that poverty and weak rule of law, more than gun laws alone, correlate with elevated homicide rates. Conclusions: Reducing gun violence sustainably requires a multifaceted approach. Authors advocate for investments in trauma-informed mental health care, focused deterrence programs, early childhood interventions, and improved enforcement against illegal gun trafficking. A public health strategy that integrates social reform with targeted regulation holds the greatest promise for long-term change.